STRATEGI PT.NANDA BANGUN NUSA UNTUK MEMPERTAHANKAN POSISINYA SEBAGAI MARKET LEADER DALAM AGRIBISNIS PERTAMANAN PADA HOTEL BERBINTANG LIMA DI BALI - DARMAWAN, DWI PUTRA; WIDIA, IDA BAGUS (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 1, No. 2 Juli 2001, 2012)
PT. Nanda Bangun Nusa is a success company in landscaping agribusiness, its indicated by increasing of selling and profit of the company continually in the year, and getting the biggest market share until the company able to get position as Market Leader in landscaping agribusiness, especially in five stars hotel in Bali. This research has aim to analysis marketing strategy of PT.Nanda Bangun Nusa to sustaining market leader position in landscaping agribusiness of five stars hotel in Bali. This research use integrated analysis such as: a. Factor Internal External Matrix, b. Profile Competitive Matrix and Mapping, c. BCG Matrix, d. Internal External Matrix (IE Matrix), e. Space and Vector Line Matrices, f. Marketing Mix-SWOT Combination Matrix, and g. SWOT Matrix. The result of research shows that the company able to apply differentiation focus strategy to ward off the treatment, impressing of competitor and the other factor external that is difficult to overcome, to sustain the highest market share and market leader position in industry landscaping of five stars hotel in Bali. This company is able to apply strong price strategy and product superiority, which is always guarded and supported by strong distribution strategy. However, the weak promotion strategy needs to straighten to sustain the highest market share and market leader position. To anticipate the condition of dynamic market, the company able to use sustainable competitive advantages, such as special characteristic of design traditional Balinese and product qualities, competitive price and distribution, experience of company in selling and good reputation in service to the customer, as well as high market share to sustain its position as market leader in landscaping agribusiness of five stars hotel in Bali.
Keywords: Marketing Strategy, Market Leader, Landscaping Agribusiness, Differentiation Focus, and Competitive Advantages